2020
DOI: 10.4049/jimmunol.2000373
|View full text |Cite
|
Sign up to set email alerts
|

Function and Regulation of Noncanonical Caspase-4/5/11 Inflammasome

Abstract: Abbreviations used in this article: ASC, apoptosis-associated speck-like protein containing a caspase activation and recruitment domain; CARD, caspase activation and recruitment domain; cGAS, cyclic GMP-AMP synthase; DAMP, damage-associated molecular pattern; GBP, guanylate-binding protein; HMGB1, high-mobility group box 1; IRF, IFN regulatory factor; OMV, outer membrane vesicle; oxPAPC, oxidized 1-palmitoyl-2arachidonoyl-sn-glycero-3-phosphorylcholine; PAMP, pathogen-associated molecular pattern; STING, stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 65 publications
1
88
0
Order By: Relevance
“…Both CASP4 and CASP5 are activated by cytosolic LPS and capable of inducing pyroptosis [34]. However, the relative contribution to the pathogenesis of endotoxemia or bacterial sepsis is unclear [74]. Studies in mice have highlighted the involvement of CASP11-dependent inflammation in a wide spectrum of inflammatory diseases, such as rheumatoid arthritis, inflammatory bowel disease and neurodegenerative diseases [75].…”
Section: Discussionmentioning
confidence: 99%
“…Both CASP4 and CASP5 are activated by cytosolic LPS and capable of inducing pyroptosis [34]. However, the relative contribution to the pathogenesis of endotoxemia or bacterial sepsis is unclear [74]. Studies in mice have highlighted the involvement of CASP11-dependent inflammation in a wide spectrum of inflammatory diseases, such as rheumatoid arthritis, inflammatory bowel disease and neurodegenerative diseases [75].…”
Section: Discussionmentioning
confidence: 99%
“…The non-canonical pathway is activated by rodent caspase-11 and its human orthologs, caspase-4 and caspase-5 [24]. Interestingly, caspase-11 is less efficient in IL-1β and IL-18 processing than it is in GSDMD cleavage, and the caspases of the non-canonical pathway.…”
Section: Inflammasomes: Overviewmentioning
confidence: 99%
“…Interestingly, caspase-11 is less efficient in IL-1β and IL-18 processing than it is in GSDMD cleavage, and the caspases of the non-canonical pathway. This dual action also requires strict control to prevent pyroptosis [24]. One such control mechanism involves the transient receptor protein channel 1 (TRPC1), a non-selective ion channel, which is itself a substrate for caspase-11.…”
Section: Inflammasomes: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Canonical NLRP3 inflammasome activation is followed by the proteolytic processing and secretion of pro-inflammatory cytokines interleukin (IL)-1β and IL-18, which are important mediators of inflammatory response (3). It has been previously shown that several activators of the NLRP3 inflammasome trigger a robust vesicle-mediated protein secretion in human innate immune cells (4). This suggests that exosome secretion constitutes an essential part of the NLRP3 inflammasome-mediated immune response.…”
mentioning
confidence: 95%